The Encounter as a distinctive category of Cuban Catholic thought between 1981 and 1986 - Pernús Santiago, Julio Norberto (2025)
In the intellectual work of Cuban Catholic thought between 1981 and 1986, the possibility of an encounter was woven that helped to discover what the Revolution meant for the Catholic subject on the island. After four decades, the question of how to determine the contributions of Cuban Catholic thought based on its structure is the objective of analysis, considering the need to delve into its validity to demonstrate that the ideas that emerged at that time are more than an interpretation of the past, they are a part of the reconciliation/reflection that continues to build realities in the Cuban Catholic subject today.